2014
DOI: 10.2478/s11756-014-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome composition revealed in Characidium fishes (Characiformes: Crenuchidae) by molecular cytogenetic methods

Abstract: The W chromosome of the fishes Characidium cf. fasciatum, Characidium sp. and Characidium cf. gomesi is heterochromatic, as is usually seen in most Characidium species. Samples of W-chromatin were collected by mechanical microdissection and amplified by DOP-PCR (degenerate oligonucleotide-primed polymerase chain reaction), to be used as painting probes (DCg and CgW) and for sequence analysis. FISH (fluorescence in situ hybridization) with DCg probe painted the whole W chromosome, the pericentromeric region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… fasciatum Reinhardt, 1867 (Table 1 ), but it is also present in most Characidium species studied. The sex chromosomes in Characidium show a high degree of differentiation among species by chromosomal size, morphology, heterochromatin accumulation and presence or absence of rDNA sites ( Maistro et al 1998 , 2004 , Centofante et al 2001 , 2003 , Vicari et al 2008 , Noleto et al 2009 , Pansonato-Alves et al 2010 , 2011b , 2014 , Machado et al 2011 , Pazian et al 2013 , 2014 , Pucci et al 2014 , 2016 , Scacchetti et al 2015a , 2015b , 2015c , Serrano et al 2017 ), as exemplified in Fig. 3 .…”
Section: Supernumerary and Sex Chromosomes In Characidiummentioning
confidence: 95%
See 2 more Smart Citations
“… fasciatum Reinhardt, 1867 (Table 1 ), but it is also present in most Characidium species studied. The sex chromosomes in Characidium show a high degree of differentiation among species by chromosomal size, morphology, heterochromatin accumulation and presence or absence of rDNA sites ( Maistro et al 1998 , 2004 , Centofante et al 2001 , 2003 , Vicari et al 2008 , Noleto et al 2009 , Pansonato-Alves et al 2010 , 2011b , 2014 , Machado et al 2011 , Pazian et al 2013 , 2014 , Pucci et al 2014 , 2016 , Scacchetti et al 2015a , 2015b , 2015c , Serrano et al 2017 ), as exemplified in Fig. 3 .…”
Section: Supernumerary and Sex Chromosomes In Characidiummentioning
confidence: 95%
“…aff. C. vidali displayed similar repetitive DNA sequences among B and sex chromosomes ( Pansonato-Alves et al 2014 , Pazian et al 2014 , Scacchetti et al 2015a , Serrano et al 2016 ), while Characidium oiticicai Travassos, 1967 and C. alipioi did not show such shared sequences ( Pansonato-Alves et al 2014 , Serrano et al 2017 , respectively). Despite their molecular homology, it was demonstrated that B and W chromosomes do not form multivalent pairings during meiosis in male and female C. gomesi individuals.…”
Section: Supernumerary and Sex Chromosomes In Characidiummentioning
confidence: 98%
See 1 more Smart Citation